Changes in retinal vessel oxygen saturation using automated retinal oximetry in patients with significant carotid stenosis - Polidar, Petr; Pašková, Barbora; Karhanová, Marta; Šín, Martin; Mudroch, Tomáš; Dorňák, Tomáš; Schreiberová, Zuzana; Divišová, Petra; Veverka, Tomáš; Franc, David; Hluštík, Petr; Šanák, Daniel; et al. (Frontiers in Neurology, 2025)
PurposeTo evaluate the dynamics of changes in retinal oximetry parameters in patients with haemodynamically significant carotid stenosis.MethodsIn this case-control study we examined 74 eye artery pairs in 37 patients with significant carotid stenosis over 50% using retinal oximetry. Fourteen eye artery pairs were excluded due to contraindications for oximetry or presenting carotid occlusion. From the remaining 60 eye artery pairs, 39 eye artery pairs formed the case group, remaining 21 pairs formed control group. Only 16 patients were eligible for bilateral testing to eliminate the possible influence of systemic comorbidities. Linear multiparametric model was used to predict the impact of the stenosis severity on retinal oximetry in context of systemic comorbidities.ResultsPaired testing did not show any significant change in AV difference between stenotic and non-stenotic sides in 16 patients eligible for bilateral testing. The predictive model estimated weak correlation between increasing AV difference in increasing stenosis severity, with significant influence of atrial fibrillation and systemic atherosclerosis among noted comorbidities.ConclusionThe relationship between oxygen extraction in retina and increasing severity of the carotid stenosis is weak and modified by various individual factors, notably comorbidities.